Nursing interventions to prevent post-traumatic stress disorders in people in intensive care: scoping review protocol - Andrade, Débora (2023)
Introduction: People who need hospitalization in Intensive Care (CI) are people exposed to stress factors, because it is a limited physical context, with artificial light and permanent noise. Added to these factors is the hostile and emotionally exhausting environment resulting from the complexity of the care needed for the person in a critical situation (Correia, 2020), making them vulnerable and at risk of developing Post Traumatic Stress Disorder (PTSD). There is currently a vast literature on PTSD, however, existing research on the role of nurses in the prevention of SPT in people hospitalized in CI is scarce. Objetive: To map nursing knowledge on nursing interventions that help prevent PTSD in inpatients in the context of CI. Methods: Scoping Review according to the Joanne Briggs Institute’s (JBI) methodology. The research strategy will map published studies. The databases included will be: PUBMED, CINAHL via EBSCO, JBI Database of Systematic Reviews, COCHRANE Database of Systematic Reviews, Portuguese Open Access Scientific Repository, OpenGrey and Dart-Europe. This review will integrate articles focusing on nursing interventions that help prevent post-traumatic stress disorder in inpatients in the context of intensive care and will include quantitative, qualitative or mixed studies, as well as systematic reviews, guidelines and gray literature. Results:  It is hoped to identify the nursing interventions that are determinant for the prevention of PTSD in inpatients in the context of CI Conclusion: The results of this review will show the role of nursing in the prevention of PTSD of the inpatient in the context of CI, raising awareness of this issue, specifically to achieve highly significant and clinically relevant outcomes in this area.